Marketing Strategies for Universities: What are Factors in Affecting Student Decisions to Study? (Case Study in Universitas Negeri Malang) - Firmansyah, Rizky; Suyono, Suyono (Ekonomi Bisnis, 2023)
The increasing public interest in higher education makes universities in Indonesia faced with opportunities and challenges to compete. Every university needs to understand the needs of students and provide optimal service to students in order to have a competitive advantage. The purpose of this study was to analyze the factors that influence students in choosing Universitas Negeri Malang through independent variables, namely perception of cost, perception of facilities and resources, university reputation, student received information, advice of relatives, and the dependent variable student decision. The type of data used in this research is quantitative with the SEM-PLS method with a research sample of 134 respondents from Universitas Negeri Malang students. The results of this study indicate that there is a significant positive effect on the perception of facilities and resources and university reputation on student decision. While in the perception of cost, student information, advice of relatives there is no influence on student decision.